Factors associated with the frequency of listening to Radio IKIM - Nur Zalifah binti Mohd Faiz (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
Radio as a source of information about Islam is not a new phenomenon in Malaysian society. Although there were some religious radio programs broadcasted over the radio in Malaysia under Radio Malaya and Radio Television Malaysia, there was never an attempt to run a religious radio station by itself until the year 2001, when the first religious radio station was set up under IKIM ('Institut Kefahaman Islam Malaysia' or The Institute of Islamic Understanding Malaysia). This radio station known as Radio IKIM, dedicates itself to the broadcasting of Islamic religious programs according to its stated objective - "The continuos effort of producing quality audio programs to promote Islamic understanding to society." Based upon the abovementioned perspective, this study had been designed to achieve the following objectives. (1) to find out the factors related to frequency of listening to Radio IKIM (2) To find out the frequency of listening to program of Radio IKIM (3) To find out the reasons for listening to program of Radio IKIM (4) To find out the amount of religious knowledge or information gained from listening to program of Radio IKIM (5) To find out other sources of religious information used by listeners of Radio IKIM and (6) To find out the effect of the programs on the listeners. The method used to collect data was by distributing 300 questionnaires to the Malaysian academic and administrative staff of International Islamic University Malaysia (IIUM), Gombak campus. Out of the 300 questionnaires distributed, only 188 or 62% of the respondents returned the questionnaires. The sample was selected randomly from a list of Malaysian academic and administrative staff serving at the Gombak campus and out of 949 staff members, every third person was chosen as a respondent. The data was collected using an interview schedule which was divided into six (6) parts or sections. In general, four (4) hypotheses related to the findings were tested. However, all of the hypotheses were not supported due to several reasons which the researcher had stated in the summary of the findings.